Reduced modulation of scanpaths in response to task demands in posterior cortical atrophy. (February 2015) - Shakespeare, Timothy J.; Pertzov, Yoni; Yong, Keir X.X.; Nicholas, Jennifer; Crutch, Sebastian J.
Abstract: A difficulty in perceiving visual scenes is one of the most striking impairments experienced by patients with the clinico-radiological syndrome posterior cortical atrophy (PCA). However whilst a number of studies have investigated perception of relatively simple experimental stimuli in these individuals, little is known about multiple object and complex scene perception and the role of eye movements in posterior cortical atrophy. We embrace the distinction between high-level (top-down) and low-level (bottom-up) influences upon scanning eye movements when looking at scenes. This distinction was inspired byYarbus (1967), who demonstrated how the location of our fixations is affected by task instructions and not only the stimulus' low level properties. We therefore examined how scanning patterns are influenced by task instructions and low-level visual properties in 7 patients with posterior cortical atrophy, 8 patients with typical Alzheimer's disease, and 19 healthy age-matched controls. Each participant viewed 10 scenes under four task conditions (encoding, recognition, search and description) whilst eye movements were recorded. The results reveal significant differences between groups in the impact of test instructions upon scanpaths. Across tasks without a search component, posterior cortical atrophy patients were significantly less consistent than typical Alzheimer's disease patients and controls in where they were looking. By contrast, when comparing search and non-search tasks, it was controls who exhibited lowest between-task similarity ratings, suggesting they were better able than posterior cortical atrophy or typical Alzheimer's disease patients to respond appropriately to high-level needs by looking at task-relevant regions of a scene. Posterior cortical atrophy patients had a significant tendency to fixate upon more low-level salient parts of the scenes than controls irrespective of the viewing task. The study provides a detailed characterisation of scene perception abilities in posterior cortical atrophy and offers insights into the mechanisms by which high-level cognitive schemes interact with low-level perception. Highlights: We investigated eye movements of PCA patients when viewing scenes. The effects of bottom-up and top-down influences were examined. PCA patients fixated upon regions of greater low-level salience than controls. PCA patients showed reduced task appropriate modulation of scanpaths.